THE EFFECT OF DIRECTED READING THINKING ACTIVITY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 2 TELUK KUANTAN IN READING COMPREHENSION - Sista Khairunnisa; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to finding out whether there is a significant effect of Directed Reding Thingking Activity strategy on the ability of first year students of SMAN 2 Teluk Kuantan in reading comprehension. The research design was a pre-experimental research with one group pre-test and post-test design. The sample was X IS was chosen by using cluster random sampling technique. The result showed that the mean score of post-test (76.00) was higher than mean score of pre-test (70.03). The value of t-test (15.48) was higher than t-table (2.04) at 5% of the significance level. Therefore, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It could be concluded that there was a significant effect of Directed Reading Thingking Activity strategy on the ability of first year students of SMAN 2 Teluk Kuantan in reading comprehension.Key Words: Directed Reading Thingking Activity, Reading Comprehension